Inquiry Based Learning Module to Empower Cooperation Skills - Dewi Anjani; Maridi Maridi; Suciati Suciati (Journal of Education and Learning (EduLearn), 2018)
The education in the 21st century focuses on knowledge and encourages students to generate information and encourage developing new skills. The framework of 21st century learning skill  is communication, collaboration, critical thinking, creativity and innovation. Cooperation skills in the world of education is an important thing to be done in learning. Therefore, a solution is needed to optimize student empower cooperation skills process by using the teaching material in the form of module. The objective of this research is to know the effectiveness of inquiry based learning module to empower cooperation skills. This research was conducted in one of high school in Surakarta, Indonesia. The research method is quasi experiment, used pretest and posttest design by using two randomly selected classes those were experimental class used an inquiry based learning module and control one used a modules made by biology teachers in Surakarta. The results showed that there were significant differences of learning outcomes between the control and the experimental classes based on the independent samples t-test test results, also seen with the n-gain scores that obtained at 0.78 (middle) in the control class and 0.87 (high) in the experimental class. As the study concluded, using inquiry based learning module in the learning process in effective to empower cooperation skills.